1991
DOI: 10.1111/j.1476-5381.1991.tb12544.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression of miniature endplate potential frequency by acetylcholine and its analogues in frog

Abstract: of Tatarstan, U.S.S.R.1 Acetylcholine (ACh), 7.5 x 10-5M, and carbachol, 5 x 10-6M (CCh) depressed the frequency of miniature endplate potentials (m.e.p.ps) in the frog (Rana temporaria) sartorious neuromuscular junction with active acetylcholinesterase to about 50-55% of the controls. 2 A similar depression was produced by the nicotinic agonists, nicotine, suberyldicholine and tetramethylammonium. 3 The muscarinic agonists, oxotremorine, methylfurmethide and methacholine were without effect on m.e.p.p. freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…Subsequent application of CCh led also to a decrease in frequency with good post-washout recovery, in accord with our previous data (Bukharaeva et al 1986;Nikolsky et al 1991a An example of miniature endplate potentials recorded from a single fibre. A: left traces, control; middle traces, 30 min after 1 ² 10¦Ê m á_bungarotoxin (BTX); right traces, 30 min after BTX was washed out and 5 ² 10¦É m carbachol had been added to the Ringer solution (CCh after BTX).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Subsequent application of CCh led also to a decrease in frequency with good post-washout recovery, in accord with our previous data (Bukharaeva et al 1986;Nikolsky et al 1991a An example of miniature endplate potentials recorded from a single fibre. A: left traces, control; middle traces, 30 min after 1 ² 10¦Ê m á_bungarotoxin (BTX); right traces, 30 min after BTX was washed out and 5 ² 10¦É m carbachol had been added to the Ringer solution (CCh after BTX).…”
supporting
confidence: 90%
“…We demonstrated that CCh decreases the mEPP frequency by 30%, even when Ca¥ was removed from Ringer solution and when Ca¥ was increased to 7 mÒ. (Nikolsky et al 1991a). To compare the CCh-and BTX-induced decrease in spontaneous quantal release, the action of BTX in Ca¥-free solution was tested.…”
Section: Btx In Low and High Ca¥mentioning
confidence: 73%
See 2 more Smart Citations
“…They are released from the motor nerve terminal and perform autoregulation of the neurosecretory apparatus [2,5,6]. However, molecular mechanisms of the inhibitory effect of these neurotransmitters remain unclear.…”
mentioning
confidence: 99%